2020
DOI: 10.1039/c9sc06221a
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of chloroauric acid with histidine in microdroplets yields a catalytic Au–(His)2complex

Abstract: Microdroplets form the Au–(His)2 complex for catalyzing the reaction of phenylacetylene and indoline, which cannot occur in bulk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 68 publications
1
23
0
Order By: Relevance
“…These results are consistent with a balance between reagent solubility, methanol evaporation and formation of a superacid surface layer of water in the almost fully evaporated microdroplets. This clearly aligns with literature data [47][48][49] on the high acidity of the surfaces of aqueous droplets while extending the concept of superacid formation in microdroplets to organic/ aqueous mixed solvents. We imagine that water, being a stronger base than methanol, takes the charge and occupies the surface of a small methanol droplet thereby protonating neutral formic acid and initiating the benzimidazole synthesis.…”
Section: Solvent Effectssupporting
confidence: 90%
See 1 more Smart Citation
“…These results are consistent with a balance between reagent solubility, methanol evaporation and formation of a superacid surface layer of water in the almost fully evaporated microdroplets. This clearly aligns with literature data [47][48][49] on the high acidity of the surfaces of aqueous droplets while extending the concept of superacid formation in microdroplets to organic/ aqueous mixed solvents. We imagine that water, being a stronger base than methanol, takes the charge and occupies the surface of a small methanol droplet thereby protonating neutral formic acid and initiating the benzimidazole synthesis.…”
Section: Solvent Effectssupporting
confidence: 90%
“…It is known that the proton concentration at the surface of positively charged electrosprayed aqueous droplets is much higher than in the bulk. [47][48][49] So we propose that a very high proton concentration at the surface of a droplet containing water will protonate neutral formic acid to create the electrophilic carbon (2a) which is subject to nucleophilic attack by the lone electron pair of the amine. (We observed protonated formic and triuoracetic acid in the mass spectra ( Fig.…”
Section: Mechanism (Scheme 2)mentioning
confidence: 99%
“…The protonated carbon dioxide and deprotonated amine reactions are of special interest because these forms of the reagents could arise from superacid/superbase reactions at the interface as discussed in the Introduction. 28 Previous reports 28,[30][31][32][33][34] have suggested that superacid (extreme pH) at the interface of organic droplets (and dielectric layers at the interface of water microdroplets) accelerate reactions. These results indicated the importance of water, even traces of water 28 in interfacial microdroplet chemistry.…”
Section: Further Mechanistic Considerationsmentioning
confidence: 99%
“… 35 In these circumstances, the hydronium ion appears to act as a superacid. 32 Significantly, even for organic solvents, trace amounts of water have been implicated in reaction acceleration, e.g. in benzimidazole formation from aromatic diamines and simple carboxylic acids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation